WOMEN INVOLVEMENT IN UNIVERSITY GOVERNANCE AND INCLUSIVE LEADERSHIP - Anda Usman Obansa; Fatima Abubakar (International Studies Journal)
The involvement of women in university governance has become a crucial marker of progress toward inclusive and equitable leadership in higher education. Despite global advances in gender equality, the participation of women in decision-making positions within universities remains disproportionately low. This paper examines the extent, challenges, and implications of women's involvement in university governance, with a particular focus on inclusive leadership practices. Using a combination of literature review and empirical analysis, the study highlights how institutional cultures, gender bias, policy gaps, and leadership stereotypes have historically limited women’s roles in academic governance. It also explores the transformative potential of women leaders in promoting participatory decision-making, ethical administration, and gender-responsive policies in universities. The paper argues that inclusive leadership defined by diversity, collaboration, and equity is enriched when women are actively engaged in governance structures such as university senates, councils, and management boards. Findings suggest that increasing female representation enhances not only gender justice but also the effectiveness and responsiveness of university governance. The paper concludes with recommendations for policy reforms, mentorship programmes, and institutional frameworks that support gender-balanced leadership. These measures are essential for creating inclusive academic environments where both men and women can contribute meaningfully to institutional development and innovation.